JUDICIAL AND EXTRAJUDICIAL DEPOSITS OF FEDERAL TAXES: UPDATE BY SELIC AFTER LAW NO. 9,703/1998 (CIPEEX, 2025)
This article examines the updating regime applicable to judicial and extrajudicial deposits related to federal taxes made after the entry into force of Law No. 9,703/1998, arguing that such amounts are updated by Brazil’s SELIC rate, thereby preserving their real value and providing predictability for future release or refund. The objective is to delineate the temporal and material scope of this framework, clarify its interaction with the tax law system of interest and indexation, and highlight practical consequences for taxpayers and the Treasury. The method is doctrinal and case-law based, combining a literature review with an analysis of statutes and precedents, as well as the administrative and banking procedures applicable to deposits tied to tax disputes. The findings indicate that, for deposits made after the law came into force, SELIC operates as a single updating index, simplifying calculations, enhancing transparency for the parties, and reducing disputes over alternative indices; they also underscore the need to assess earlier deposits, which may be subject to different correction rules. The conclusion is that the legislative choice of SELIC fosters legal certainty and equal treatment among similarly situated taxpayers, while requiring verification of the deposit date and compliance with specific court orders, particularly for deposits predating the statute or in exceptional scenarios of effect modulation.
Keywords: judicial deposits; SELIC rate; monetary update; federal taxation